Acute Limb Ischemia in the Young: A Rare Case of Essential Thrombocytosis - Johanes Nugroho; Ruth Gunadi (Case Reports in Cardiology)
Acute limb ischemia (ALI) is rarely observed in young populations. The hypercoagulable state is a notable cause of ALI other than artery disease progression and cardiac embolization. A hypercoagulable state occurs in essential thrombocytosis because of the overproduction of hematopoietic cells secondary to the mutation of the JAK2, CALR, or MPL genes. We report a rare case of a 37-year-old woman presenting with Rutherford IIA ALI in the left lower extremity. Laboratory data revealed she had a platelet count reaching up to 1.38 mil/μL, with other blood profiles being normal. A JAK2 mutation examination was later performed and proved positive. After careful management with catheter-directed thrombolysis, surgical thrombectomy, and cytoreductive therapy using hydroxyurea, the symptoms subsided and eventually restored the patient to physical activity in less than one month.